Pengaruh Discharge Planning Berbasis Keluarga Terhadap Kualitas Hidup Pasien Stroke : Literatur Review - Eka Wati; Ainul Yaqin Salam; Grido Handoko Sriyono (JURNAL RISET RUMPUN ILMU KESEHATAN, 2023)
Implementing family-based discharge planning, which relies on the participation of family members, can help stroke victims feel better. The purpose of this study was to identify the effect of family-based discharge planning on the quality of life of stroke patients based on journal literature reviews. Methode uses systematic literature reviews of journals taken from research in 15 journals, which were discovered through screening results of a number of journals from Google Scholar, Cochrane, Science Direct, Pubmed, and Wile using the keywords "Discharge Planning" AND "Family" AND "Quality Of Life" AND "Stroke OR Post Stroke". Writing research journals from the 2017-2021 time frame and those that complied with inclusion and exclusion standards, in PICOTS format, both national and international journals. Results from 15 design journals used quasy experimental (33.5%), Systematic Review (13.4%), Randomized controlled (13.4%), Cross sectional survey (6.7%), Longitudinal Survey (6.7%), True Experimental (6.7%), Parallel group (13.4%), Retrospective Study (6.7%). Conclusion Discharge planning provides family caregiver education about stroke. The support of family members is very important in improving the patient's health by contributing to quality care and creating a pleasant atmosphere.